2005
DOI: 10.1111/j.1600-0684.2005.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal ultrasonography: biometric data from four African primate species

Abstract: These data, by providing a tool to evaluate precise gestational age, will be useful for centers raising these four primate species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…Diminishing wild populations, international regulations on protected species, and research requirements for animals with known health status have virtually halted sampling from wild populations and have placed the accent on captive breeding (Bourry et al 2005). Reproductive monitoring, including uterine examination, has always been a great concern in gynecology, since the uterus is the organ responsible for the maintenance of pregnancy and may be affected by various diseases that reduce fertility or cause severe damage to female health.…”
Section: Introductionmentioning
confidence: 99%
“…Diminishing wild populations, international regulations on protected species, and research requirements for animals with known health status have virtually halted sampling from wild populations and have placed the accent on captive breeding (Bourry et al 2005). Reproductive monitoring, including uterine examination, has always been a great concern in gynecology, since the uterus is the organ responsible for the maintenance of pregnancy and may be affected by various diseases that reduce fertility or cause severe damage to female health.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of the Milwaukee Formulas with earlier published data for P. troglodytes [Bourry et al, 2006] revealed that there are only minor differences between the two species. Regarding BPD, P. paniscus and P. troglodytes show a similar growth progression (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…To demonstrate the differences in prenatal growth in P. paniscus , its closest relative P. troglodytes , and humans, we compared the Milwaukee Formulas with earlier published formulas for the two other species [Bourry et al, 2006; Hadlock et al, 1984]. The absolute dimensions are displayed in simple growth graphs (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations